2003
DOI: 10.1210/en.2002-220597
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Nitric Oxide Synthase Mediates Bone Loss in Ovariectomized Mice

Abstract: Several clinical studies have shown that bone loss may be attributed to osteoclast recruitment induced by mediators of inflammation. In different experimental paradigms we have recently demonstrated that estrogen exhibits antiinflammatory activity by preventing the induction of inducible nitric oxide synthase (iNOS) and other components of the inflammatory reaction. To verify whether this could explain the estrogen-dependent blockade of osteoporosis, we investigated the effect of ovariectomy in mice in which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 38 publications
3
44
0
4
Order By: Relevance
“…It has been established that in the presence of CSF-1 sufficient to maintain cell growth and survival, RANKL, via its tumor necrosis factor family receptor RANK, is sufficient to induce complete osteoclastic differentiation from hematopoietic precursors and that knock-out mice with defects in the RANKL system cannot form osteoclasts (26). It is also established that estrogen withdrawal causes rapid skeletal degradation, an effect that certainly involves other cells, including osteoblasts, but that has also been hypothesized to involve direct effects on osteoclast formation (3)(4)(5). This report demonstrates that phytoestrogens and ␤-estradiol directly reduce osteoclastic differentiation in the murine RAW264.7 cell model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established that in the presence of CSF-1 sufficient to maintain cell growth and survival, RANKL, via its tumor necrosis factor family receptor RANK, is sufficient to induce complete osteoclastic differentiation from hematopoietic precursors and that knock-out mice with defects in the RANKL system cannot form osteoclasts (26). It is also established that estrogen withdrawal causes rapid skeletal degradation, an effect that certainly involves other cells, including osteoblasts, but that has also been hypothesized to involve direct effects on osteoclast formation (3)(4)(5). This report demonstrates that phytoestrogens and ␤-estradiol directly reduce osteoclastic differentiation in the murine RAW264.7 cell model.…”
Section: Discussionmentioning
confidence: 99%
“…3). However, transgenic and knock-out mice with varying ER␣ and ER␤ expression established that estrogen effects on bone involve ER␣ and ER␤, which modulate signaling pathways involving Erk and nitric oxide and perform direct transcriptional activity (4). Estrogen responses in mesenchymal stem cell-derived bone-forming cells, osteoblasts, are extensively studied.…”
mentioning
confidence: 99%
“…We here have shown that nNOS is sensitive to strain up-regulation and NO generation in osteoprogenitor cells -essentially "taking over" for eNOS as the mechanically regulated NO synthase to preserve normal skeletal homeostasis. Finally, in mice deficient in the inflammatory NOS isoform, iNOS, although no bone abnormalities have been described under normal conditions, iNOS deficient mice are partially protected from ovariectomy [43] and inflammatory [44] induced bone loss. Taken together, this evidence reminds us that in the normal, NO synthase replete bone cell, nitric oxide regulation of skeletal remodeling is complex.…”
Section: Discussionmentioning
confidence: 99%
“…15) Cuzzocrea et al suggest that iNOS is a potential target for therapy of postmenopausal osteoporosis in women. 24) We hypothesize that KE will be a useful agent in the treatment of osteoporosis and osteoarthritis because it has significant effects on the NO production and expression of iNOS in macrophages. We will investigate whether the anti-osteoporotic and anti-arthritic effect of KE are depressed by using the iNOS inhibitor.…”
Section: Discussionmentioning
confidence: 99%